PERANCANGAN BUKU POP-UP PENDIDIKAN PANCASILA DENGAN TEKNIK TRANSFORMATION SEBAGAI UPAYA PENGENALAN DASAR NEGARA INDONESIA UNTUK ANAK-ANAK - Sadewo, Herlin Roesmarlina; Riyanto, Darwin Yuwono; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Abstract: Pancasila is one of the assets of a nation that deserves to be maintained and preserved and given hereditary from one generation to the next is intended that the culture of a nation is not lost in the modern age that is increasingly growing, with their diversity of tribes, People and Cultures in Indonesia is not fully supported by the media information that presents to the children something exciting and new, most of the book Pancasila with something boring or old-fashioned so that the interest of the curiosity of children into declining this is what then makes Pancasila itself not so can thrive and not in demand by the general public especially the younger generation, with the times like these which greatly facilitates foreign culture to enter Indonesia be a threat to the state of Indonesia which will be the basis of the state Pancasila Indonesia will be easily forgotten because of the presence of culture foreign packed with more interesting. Instilling the values of Pancasila in children can be done in various ways. How it can be started from small things were easily captured, understood and carried out by the child. This is so that the child can be easy to do so. Thus, the children feel comfortable and happy to do without feeling overwhelmed. Due to a lack of interest in maintaining and preserving the basis of the state Pancasila itself create the next generation to forget the basic state, as an example of the precepts contained in Pancasila itself sometimes people do not know what the meaning of the content of the precepts that, even some that do not remember what sentence and the symbol of these precepts. Then it has become imperative for us as the future generation in order to participate in the case to preserve, develop and preserve the culture of the state and the nation's diverse so that later can be one of the cultural always awake. Keywords: Pop-Up Book, Education Pancasila, Engineering Transformation, A Basic Introduction Country, Language Arts.